Examining the Impact of Institutional Ownership and Audit Fee Stickiness on Tax Avoidance in State-Owned Enterprises in Indonesia (2019–2022) - Mira, Mira; Masrullah, Masrullah; Nurfadillah, Asti (Jurnal Riset Perpajakan: Amnesty, 2025)
This study examines the influence of institutional ownership and audit fee stickiness on tax avoidance in state-owned enterprises (SOEs) listed on the Indonesia Stock Exchange during the 2019–2022 period. The research adopts a quantitative approach using secondary data obtained from official financial reports and processed through multiple linear regression analysis with SPSS version 29. Institutional ownership refers to the proportion of company shares held by institutional investors such as insurance firms, investment companies, and banks, which are expected to play a critical role in monitoring managerial behavior. Audit fee stickiness, on the other hand, represents the condition where changes in expected audit fees are not matched by actual changes, often due to long-term audit engagements and client-auditor relationships. The results of this study indicate that institutional ownership has a significant positive effect on tax avoidance, suggesting that firms with high levels of institutional ownership tend to adopt more aggressive tax planning strategies. This may stem from institutional pressure to maximize shareholder value through reduced tax burdens. Additionally, audit fee stickiness also shows a significant positive relationship with tax avoidance, implying that inflexible audit pricing may reflect increased audit complexity and risk exposure, which correlate with tax-motivated financial reporting behaviors. This study contributes to the literature by providing empirical evidence on how corporate governance mechanisms and audit dynamics affect tax strategies within SOEs in a developing country context. The findings align with agency theory, which explains the conflict of interest between management (agents) and government or public stakeholders (principals), especially regarding financial transparency and tax compliance. Implications of this study are valuable for regulators and policymakers aiming to improve audit oversight and corporate governance in the public sector.